Strategi Menghafal Al-Qur’an Terhadap Keberhasilan Penghafal Al-Qur’an - Arif, Uswatun Khasanah; Rosyidi, Zudan (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
The aim of carrying out this research is to find out the strategy for memorizing the Al-Qur'an by alumni of the Amanatul Ummah Islamic boarding school quickly in completing memorizing 30 juz. The phenomenological qualitative research method is the research method used in this research, the data collection method uses the interview method. Interviews were conducted with alumni who are also memorizers of the Al-Qur'an at the Amanatul Ummah Pacet Islamic Boarding School. The results of this research show that the success of memorizing the Al-Qur'an cannot be separated from the process of memorizing the Al-Qur'an. Every memorizer of the Qur'an or resource person must have different strategies and methods. They struggle to be able to complete memorizing up to 30 juz (khatam). Many of the alumni completed memorizing the Al-Qur'an when they were in grade 12. Until now, they are trying to maintain their memorization. Not only memorizing, they also maintain the memorization that has been memorized by murajaah or repeating the memorized verses until they are fluent and not easily lost. Apart from memorizing and murajaah, the way to ensure that memorization is not lost is to take care not to commit sins, for example, such as dating someone of the opposite gender.